PENGARUH KECEMASAN TERHADAP PENGELUARAN ASI PADA IBU POST PARTUM - Faulia Mauluddina; Putri Ayu Ning Kasih (Jurnal Kesehatan dan Pembangunan, 2023)
Mother's Milk (ASI) is the best food for babies because in addition to providing all the nutritional elements needed, breast milk contains very specific components, and has been prepared to meet the needs and development of babies. Anxiety factor, whereas if the mother's mood feels comfortable and happy it will affect the smoothness of breastfeeding, on the contrary if the mother feels anxious it will inhibit the smooth flow of breast milk. The Effect of Anxiety on Breastfeeding in Post Partum Mothers at Citra Clinic Palembang in 2021. The research design used was a cross sectional design with an observational analytic approach. The sample from this study was some post partum mothers at the Citra Palembang Clinic in 2021, totaling 36 people. The results showed that the frequency distribution of respondents was based on the level of anxiety in the category of no anxiety as many as 24 respondents (66.7%), in the mild anxiety category by 10 respondents (27.8%), and in the moderate anxiety category by 2 respondents (5.6%). There were 18 respondents (50.0%) if the milk came out and 18 respondents (50.0%) if the milk didn't come out at all. The results of the bivariate analysis showed that there was an influence between the two variables of breastfeeding with the independent variable of anxiety with a p value of 0.011. It can be concluded that there is an effect of anxiety on breastfeeding in postpartum mothers at the Citra Palembang Clinic in 2021 with a p value of 0.011 (p value = 0.05). It is hoped that health workers, especially those at the Citra Clinic, can suggest or teach post partum mothers to reduce anxiety about breastfeeding